Reproductive biology, diet and feeding pattern of longtail tuna Thunnus tonggol (Bleeker, 1851) in the north-eastern Arabian Sea off Gujarat, India - Koya, K. Mohammed; Rohit, Prathibha; Abdussamad, E. M.; Azeez, P. Abdul; Vase, Vinay Kumar; Bharadiya, A. Sangita (Indian Journal of Fisheries, 2018)
Longtail tuna Thunnus tonggol (Bleeker, 1851) is the major tuna resource in the neritic realms of the northern Arabian Sea and forms considerable fishery in the coastal nations in the region. Gujarat, on the north-west coast is the major province landing longtail tuna in India. The paper attempts to add to the hitherto sparse knowledge base on biology of the longtail tuna fished along the north-west coast of India, through a study spanning from 2011 to 2015. Reproductive biology, spawning, food and feeding dynamisms of the species were investigated. Sex ratio of the species was estimated as 1:2.1 and depicted an increase in male preponderance as the size increased. The fish attains maturity at 607 mm and it spawns during summer months starting from May. The fish is typically a non-selective feeder and over 22 taxa comprising of fishes, cephalopods and crustaceans formed the diet at varying rates over the year. Variation in feeding intensity at different reproductive stages is discussed besides the constraint posed by the large presence of unidentifiable, partially digested gut content.